2021
DOI: 10.31236/osf.io/ut6zm
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

An institutional analysis of gender (in)equalities, covid-19 and governance of elite women’s football in Australia, England and USA.

Abstract: Women’s football faces an existential threat in light of covid-19. Using case studies, we explore the covid-19 responses of three highly-ranked countries’ national football associations (Australia, England, and USA) and their professional women’s football leagues to: (a) compare and shed new insights into the wide range of covid-19 responses, and (b) identify ways that other nations could successfully manage the tensions between the economic impact of covid-19 and their social and ethical responsibilities to w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 36 publications
(10 reference statements)
0
10
0
Order By: Relevance
“…The effects of COVID-19 have revealed the vulnerabilities of women's sports rather clearly [65]. It can be said that female athletes are more affected by the restrictions caused by COVID-19 due to the decrease in training times and changes in training patterns, financial problems, and difficulties in accessing sports equipment [66].…”
Section: Discussionmentioning
confidence: 99%
“…The effects of COVID-19 have revealed the vulnerabilities of women's sports rather clearly [65]. It can be said that female athletes are more affected by the restrictions caused by COVID-19 due to the decrease in training times and changes in training patterns, financial problems, and difficulties in accessing sports equipment [66].…”
Section: Discussionmentioning
confidence: 99%
“…More recently conducted research has compared the Covid-19 responses of different national football associations: Australia (Football Federation of Australia: FFA), England (the FA) and the USA (U.S. Soccer Federation: USSF) over the first six months of the pandemic (Clarkson et al, 2021). The authors found a wide range of responses that were deeply rooted in their historical, social and political contexts.…”
Section: Footballmentioning
confidence: 99%
“…Consequently, Clarkson et al (2021) identified ways that other nations could successfully manage the tensions between the economic impact of Covid-19 and their social and ethical responsibilities to women's football. The authors recommended that nations: (1) maintain active communication with the community to allay worries about the future of women's football, (2) gather support from health and government officials, (3) seek out commercial and broadcasting partnerships to drive revenue, and (4) the interests of women's football are best served when responsibility for the elite women's league does not rest (solely) with national football associations.…”
Section: Uncorrected Proofmentioning
confidence: 99%
“…When men’s football returned in England via the resumption of the Premier League (EPL), albeit without fans, it reinstated a leisure routine in many people’s lives and maintained social connections within communities in times of isolation ( Parnell et al, 2020 ). Particularly significant as an indicator of the importance placed on women’s football, though, was the cancellation of all women’s football competitions during this time ( Clarkson et al, 2021a ).…”
Section: Introduction: Framing Women’s Footballmentioning
confidence: 99%
“…Nonetheless, there has been a positive shift in the last few years towards media reporting of women’s sport, in particular women’s football ( Petty & Pope, 2019 ), that is aligned with widespread growth of the game. The cancellation of women’s football in England, while the top two tiers of men’s football returned, has been identified as of key concern by scholars ( Clarkson et al, 2020 ; Clarkson et al, 2021a ). This empirical study examines British media coverage of women’s football during the first 6 months of the COVID-19 pandemic, in order to identify how the media framed the women’s game and how those frames could shape public perceptions of women’s football.…”
Section: Introduction: Framing Women’s Footballmentioning
confidence: 99%